Pembuatan Sistem Pengkabutan Otomatis dengan Kontrol Suhu Air dan Suhu Udara Berbasis IoT - Khafiyyan, Farih; Novianty, Inna (Faculty of Industrial Technology Universitas Islam Indonesia, 2024)
This research aims to overcome the challenge of excessive temperatures in hydroponic gardens by implementing a temperature and water temperature control system. The main problems identified were excessive temperatures in the hydroponic environment and the need for effective methods for monitoring and controlling the water temperature in the garden. This research focuses on overcoming excessive temperatures by using a misting system that can provide efficient water use and maintain water temperature and temperatures in accordance with ideal standards for hydroponic plants. In addition, this research seeks solutions to accurately monitor the temperature of hydroponic garden water and build a control device that allows remote regulation to achieve ideal environmental conditions. Implementing this solution is hoped to increase the productivity and health of hydroponic plants in an optimal environment. Data collection and analysis were conducted to obtain a Mean Square Error value of 1.33, indicating that the average square model prediction error was 1.33 degrees. The Root Mean Squared Error value of 1.15 indicates that the root mean squared model prediction error is 1.15°C, and the r-squared value obtained is 0.86, indicating that this regression model can explain 86% of the observed air temperature variations.